Environmental based social studies learning reconstruction in developing social skills during the COVID-19 pandemic - Indrianisari, Bakti; S, Dewi Liesnoor; Priyanto, Agustinus Sugeng (JESS (Journal of Educational Social Studies), 2022)
Utilization of the environment is a learning approach that seeks to increase student involvement through the utilization of the environment as a learning resource. The purpose of this study is to analyze the lesson preparation plan, implementation of learning and assessment of environmental-based social studies learning in developing social skills of junior high school students during the Covid-19 Pandemic. This study uses qualitative research methods, namely research that produces descriptive data. This research was conducted by taking locations in SMPN 1, SMPN 3 and SMPN 12 Pekalongan. Data collection techniques are in-depth interviews, observation, and documentation. The data that has been collected is then analyzed using qualitative descriptive analysis. The data that has been collected will be interpreted with source triangulation and technical triangulation. The results obtained from the research that environmental-based social studies learning can improve students' social skills during the covid-19 pandemic. The development of students' ideas and intellect can be more optimal when students are able to take advantage of their environment as a learning resource